I dispositivi e la possibilità di aprire luoghi d'abitare. Una riflessione a partire dalle "cose" di Heidegger - Gifuni, Alessia (S&F_scienzaefilosofia.it)
Devices and the Possibility of Opening Habitable Spaces: A Reflection Inspired by Heidegger's "Things" This paper aims to thematize the redefinition of the dynamics of location implied in the use of digital devices. We will start from a particular conception of entities, understood as “things,” a reading that reconnects entities to their capacity to constitute places to be inhabited. We will first clarify the link that ontologically holds things and places together, in light of which we will ask whether a technological device can be understood as a “thing”. This clarification will lead us to the difference between the dimensionality of the world and the two-dimensionality of its image, which the user enjoys through devices. We will understand, then, what kind of horizon devices are capable of presentifying, asking whether in fact they lead the experience to an “elsewhere,” in light of the current narrative on the topic, which interprets from this hermeneutic category- “elsewhere” -the space made possible by the digital. This path will construct an answer to the question about the dynamics of localization, which may be, in the case of digital devices, de-localizing, dis-locating or dislocating into a delocalization.